Climate change vulnerability and drivers of low maize yields under smallholder farming systems in semi-arid area of Marange in Zimbabwe - Muoni, Tarirai; Kihara, Job; Madamombe, Sandra M.; Öborn, Ingrid; Nyamadzawo, George; Thierfelder, Christian; Chirinda, Ngonidzashe; Ng’ang’a, Stanley Karanja; Nkurunziza, Libère (Springer, 2025)
In semi-arid regions, smallholder farmers are vulnerable to the impacts of climate change due to naturally low rainfall. However, regardless of their vulnerability, farmers continue to grow maize (Zea mays L.) under rain-fed systems even though the chances of crop failures are very high, and their yields remain extremely low. This study used on-farm data to investigate how agronomic management practices chosen by farmers influence maize productivity in rain-fed smallholder farming systems in the semi-arid Marange area of Mutare district, Zimbabwe. A sample of 107 farmers were interviewed at household level. The collected information included socio-ecological data and maize yield data from small plots on each farm of an interviewed household. The results showed extremely low maize yields, ranging from 90 to 970 kg ha−1 and an average of 355 kg ha−1. Several agricultural practices, including the strategic choice for where to plant the maize, the use of planting basins, weed management, and mulching, contributed to differences in maize yields among households. Socio-economic factors including access to agricultural information (market- and production-related), weather information services, and exposure to extension officers and researchers, enabled farmers to learn and achieve better maize yields. We conclude that maize yields are still terribly low, requiring additional efforts to develop measures that improve the production in these vulnerable communities. While most of the selected agronomic practices showed significant differences, overall yields were still low. A comprehensive overhaul of agronomic practices, land management practices, extension services, and access to weather and climate information is needed to sustainably improve maize productivity in smallholder farming systems vulnerable to climate variability and change.